2011
DOI: 10.1007/s11274-011-0917-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different malolactic fermentation inoculation scenarios on Riesling wine aroma

Abstract: During malolactic fermentation (MLF), lactic acid bacteria influence wine aroma and flavour by the production of volatile metabolites and the modification of aroma compounds derived from grapes and yeasts. The present study investigated the impact of different MLF inoculation strategies with two different Oenococcus oeni strains on cool climate Riesling wines and the volatile wine aroma profile. Four different timings were chosen for inoculation with bacteria to conduct MLF in a Riesling must/wine with a high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
42
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 18 publications
15
42
0
5
Order By: Relevance
“…The final concentrations of ethanol obtained in the vinification with alcoholic fermentation only (AF) did not differ considerably from those obtained in the other variants of the process (COI, SEQI, and SPONT) ( Table 3). This result confirms the observations of other authors who have reported no disturbances to alcoholic fermentation when employing similar bacterial inoculation variants [1,14,19,30,39,43]. Although some authors have pointed to disturbances in alcoholic fermentation attributed to the activity of malolactic bacteria, these have concerned the viability of the yeast-a reduction in their growth dynamics and metabolic activity-with no significant influence on the final ethanol content in wines [7,34].…”
Section: Impact Of Mlf On Alcoholic Fermentationsupporting
confidence: 90%
See 2 more Smart Citations
“…The final concentrations of ethanol obtained in the vinification with alcoholic fermentation only (AF) did not differ considerably from those obtained in the other variants of the process (COI, SEQI, and SPONT) ( Table 3). This result confirms the observations of other authors who have reported no disturbances to alcoholic fermentation when employing similar bacterial inoculation variants [1,14,19,30,39,43]. Although some authors have pointed to disturbances in alcoholic fermentation attributed to the activity of malolactic bacteria, these have concerned the viability of the yeast-a reduction in their growth dynamics and metabolic activity-with no significant influence on the final ethanol content in wines [7,34].…”
Section: Impact Of Mlf On Alcoholic Fermentationsupporting
confidence: 90%
“…Tristezza et al [39] reported a significant reduction in volatile acidity (0.30-0.31 g/L) as a result of simultaneous yeast and bacteria inoculation, in comparison to sequential inoculation (0.49-0.51 g/L). A similar trend was noted by Knoll et al [19] in the vinification of cool-climate Riesling: for the four MLF inoculation timings tested (24 h after yeast inoculation and after 40, 60, and 100% of alcoholic fermentation completion), the concentration of acetic acid in the final wine increased from 0.61 to 0.77 g/L, respectively.…”
Section: Citric and Acetic Acid Metabolismsupporting
confidence: 85%
See 1 more Smart Citation
“…Dla porównania, w hiszpańskich winach Tempranillo i Merlot stwierdzono obniżenie kwasowości po MLF, odpowiednio: z 3,99 do 3,03 ÷ 3,53 g/l oraz z 5,13 do 3,65 ÷ 4,23 g/l kwasu winowego w zależności od użytego szczepu O. oeni [5]. Z kolei w białych winach zimnego klimatu po MLF odnotowano istotne zmniejszenie kwasowości [16]. Powodem tak wysokiej kwasowości badanych win mogły być warunki pogodowe w czasie dojrzewania winogron.…”
unclassified
“…Na zawartość polifenoli wpływ mają: odmiana winogron, stopień dojrzałości oraz nasłonecznienie w czasie dojrzewania owoców. Wina krajowe, z powodu krótkiego okresu wegetacyjnego i mniej sprzyjających warunków pogodowych, odznaczają się mniejszą zawartością polifenoli w porównaniu z winami pochodzącymi z krajów o cieplejszym klimacie [7,14,16].Powodem wzrostu ilości związków polifenolowych podczas odkwaszania mogła być również aktywność enzymatyczna bakterii oraz mała specyficzność metody. O. oeni wykazuje niewielką zdolność do syntezy lotnych związków fenolowych, jednak ma enzymy hydrolizujące polimery flawanoli, a także wykazuje aktywność β-glukozydazy.…”
unclassified